'A beautiful and living picture': translation, biography, reception, and feminism in Maria Roscoe's Vittoria Colonna: her life and poems (1868). (3rd April 2018) - Strowe, Anna
ABSTRACT: Translation and biography have been recognized as offering opportunities historically for women to participate in public literary life. This article explores an 1868 biography of Vittoria Colonna,  by Maria Roscoe, which includes translations of some of Colonna's poems. The translations and the text itself, taken as forms of rewriting, are used alongside a reader's report and contemporary book reviews to highlight how Roscoe's work paradoxically adhered to traditional notions of femininity while using that adherence as a means to explore less traditional notions. Roscoe's portrayal of her subject and herself in conservative terms creates the textual space to propose and embody less conservative ideas regarding women's role as writers, engaging directly with not only traditionally feminine topics, but writing biographies of men and "serious" histories. Key to this portrayal are the translated poems, which tie together the biography and provide evidence for Roscoe's assertions. The tension between tradition and novelty connects to tensions between Victorian feminist and anti-feminist writing that have been observed in the context of the novel; this analysis looks at how translation fits into those ideological negotiations. Furthermore, the case itself exemplifies the possibilities of connecting translation analysis to investigation of processes of book publication and reception.